Altered trabecular bone structure and delayed cartilage degeneration in the knees of collagen VI null mice. - Susan E Christensen; Jeffrey M Coles; Nicole A Zelenski; Bridgette D Furman; Holly A Leddy; Stefan Zauscher; Paolo Bonaldo; Farshid Guilak (PLoS ONE)
Mutation or loss of collagen VI has been linked to a variety of musculoskeletal abnormalities, particularly muscular dystrophies, tissue ossification and/or fibrosis, and hip osteoarthritis. However, the role of collagen VI in bone and cartilage structure and function in the knee is unknown. In this study, we examined the role of collagen VI in the morphology and physical properties of bone and cartilage in the knee joint of Col6a1(-/-) mice by micro-computed tomography (microCT), histology, atomic force microscopy (AFM), and scanning microphotolysis (SCAMP). Col6a1(-/-) mice showed significant differences in trabecular bone structure, with lower bone volume, connectivity density, trabecular number, and trabecular thickness but higher structure model index and trabecular separation compared to Col6a1(+/+) mice. Subchondral bone thickness and mineral content increased significantly with age in Col6a1(+/+) mice, but not in Col6a1(-/-) mice. Col6a1(-/-) mice had lower cartilage degradation scores, but developed early, severe osteophytes compared to Col6a1(+/+) mice. In both groups, cartilage roughness increased with age, but neither the frictional coefficient nor compressive modulus of the cartilage changed with age or genotype, as measured by AFM. Cartilage diffusivity, measured via SCAMP, varied minimally with age or genotype. The absence of type VI collagen has profound effects on knee joint structure and morphometry, yet minimal influences on the physical properties of the cartilage. Together with previous studies showing accelerated hip osteoarthritis in Col6a1(-/-) mice, these findings suggest different roles for collagen VI at different sites in the body, consistent with clinical data.